Texture of Serra da Estrela cheeses from different dairies - Guiné, Raquel (2019)
Serra da Estrela cheese is the most appreciated of Portuguese traditional cheeses. Because its texture is one of its most valued attributes, the purpose of this work was to compare the textural properties of Serra da Estrela cheese manufactured in six different dairies by three tests: spreadability, puncture and compression. The results obtained allowed concluding that the samples presented different textural properties in regards to some parameters, while being similar for others. For example, the hardness and chewiness of the crust were fairly variable, while the springiness and cohesion were very similar in all samples. Also, the results indicated that the properties of the crust were autonomous in relation to those of the inner paste. Finally, from the analysis of the relations between the studied properties, only the correlation between hardness in both tests was found strong (correlation significant at p < 0.05). In conclusion, the results obtained proved the usefulness of using different methodologies to evaluate cheese texture, in a way that these three types of test are complementing in the definition of the texture profiles of the cheeses.